Investigating L2 writing processes across independent and integrated tasks: A mixed-methods study. (July 2020) - Michel, Marije; Révész, Andrea; Lu, Xiaojun; Kourtali, Nektaria-Efstathia; Lee, Minjin; Borges, Lais
Most research into second language (L2) writing has focused on the products of writing tasks; much less empirical work has examined the behaviours in which L2 writers engage and the cognitive processes that underlie writing behaviours. We aimed to fill this gap by investigating the extent to which writing speed fluency, pausing, eye-gaze behaviours and the cognitive processes associated with pausing may vary across independent and integrated tasks throughout the whole, and at five different stages, of the writing process. Sixty L2 writers performed two independent and two integrated TOEFL iBT writing tasks counterbalanced across participants. While writing, we logged participants' keystrokes and captured their eye-movements. Participants took part in a stimulated recall interview based on the last task they had completed. Mixed effects regressions and qualitative analyses revealed that, apart from source use on the integrated task, L2 writers engaged in similar writing behaviours and cognitive processes during the independent and integrated tasks. The integrated task, however, elicited more dynamic and varied behaviours and cognitive processes across writing stages. Adopting a mixed-methods approach enabled us to gain more complete and specific insights than using a single method.